Ambidextrous Leadership dan Transformasi Digital: Sebuah Kerangka Kerja Strategis untuk Keunggulan Kompetitif di Masa Depan - Nasrulloh Nasrulloh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to develop a strategic framework integrating ambidextrous leadership with digital transformation to create organizational competitive advantage. Employing a narrative literature review approach, the study analyzes academic publications from 2021-2025 across reputable databases. Analysis results identify that ambidextrous leadership operates through dynamic balance between exploration and exploitation behaviors mediated by innovation capabilities, organizational learning, and organizational resilience. The effectiveness of ambidextrous leadership is moderated by contingency factors including digital maturity, environmental dynamism, organizational size, and technological complexity. The developed framework integrates resource-based view perspective, dynamic capabilities theory, and organizational ambidexterity literature into an operational holistic model. Implementation strategies encompass strategic vision establishment, ambidextrous organizational structure development, digital culture transformation, balanced performance measurement systems, and ecosystem partnerships. This research provides theoretical contribution in enriching strategic leadership literature and practical contribution as implementative guidance for organizations in accelerating digital transformation toward sustainable competitive advantage.